2019
DOI: 10.3390/ma12223798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copper Ion Concentration on Bacteria and Cells

Abstract: In the oral cavity, dental implants—most often made of commercially pure titanium—come in contact with bacteria, and antibacterial management has been researched extensively to improve patient care. With antibiotic resistance becoming increasingly prevalent, this has resulted in copper being investigated as an antibacterial element in alloys. In this study, the objective was to investigate the copper ion concentrations at which cyto-toxicity is avoided while bacterial inhibition is ensured, by comparing Cu ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…The bacteria test gave an interesting result after two hours of exposure for the alloys, and 10Cu400 had an antibacterial rate R of 11%, while all the other Ti-Cu x alloys had higher mean luminescence than CPTi. The reason for the higher luminescence could be that the bacteria underwent a stress response, which caused a rapid increase in population [23]. Comparison of the aged alloys at two hours and at six hours gave a similar trend for antibacterial rate (R).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The bacteria test gave an interesting result after two hours of exposure for the alloys, and 10Cu400 had an antibacterial rate R of 11%, while all the other Ti-Cu x alloys had higher mean luminescence than CPTi. The reason for the higher luminescence could be that the bacteria underwent a stress response, which caused a rapid increase in population [23]. Comparison of the aged alloys at two hours and at six hours gave a similar trend for antibacterial rate (R).…”
Section: Discussionmentioning
confidence: 95%
“…It has been demonstrated that a higher Cu content yields a better antibacterial response [17], however, an excess of copper can be harmful to the human body [42]. Previous studies [15,23] have reported that the Cu ions released from alloys with up to 10 wt% Cu did not have any notable toxic effects and were therefore the focus of the present study. Moreover, only two heat treatments were studied due to a necessary delimitation of the study.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations